Allied health management of technology‐related musculoskeletal complaints among children and adolescents. (16th September 2016) - Ciccarelli, Marina; Fraser, Kerri; Vaz, Sharmila
Abstract : Background/aim: Children and adolescents are prolific users of information and communication technologies (ICT) in learning, leisure, and social communication activities. High exposure to ICT is associated with musculoskeletal injuries in adults; however, the management of ICT physical complaints in children is not well‐understood. Methods: An online survey of allied health professionals (occupational therapists, physiotherapists, and chiropractors) was undertaken to determine (i) the number of children and adolescents in Perth, Western Australia who accessed treatment for musculoskeletal complaints related to use of technology; (ii) the typical frequency and duration of service provision; and (iii) the nature of treatment provided. Costs associated with service provision were estimated. Results: Data from 101 identified the most commonly treated musculoskeletal complaints among children and adolescents included: non‐specific neck pain; thoracic postural pain disorder; non‐specific low back pain; and lumbar postural pain disorder. Approximately 1445 children were treated in the previous 12 months; with one‐third of chiropractors each reported treating 31+ children. Most common treatments were soft tissue release, mobilisation, flexibility and conditioning exercises, soft tissue massage and kinesio‐taping. Verbal education about healthy use of technology was provided by most clinicians (88%), with some inconsistent recommendations. The estimated cost of treatment was AUD1, 057, 715; of which AUD544, 886 was health system funded. Conclusions: Children and adolescents received allied health treatment for a range of musculoskeletal complaints associated with ICT use. The potential long‐term impacts on their health and wellbeing, and the economic burden associated with this health issue warrant the development of systematic risk reduction strategies.